2007
DOI: 10.1007/s10826-007-9142-5
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Health and Safety among Homeless Youth

Abstract: This study examines how substance use is associated with the health and safety of homeless youth using cross-sectional, self-report data from 285 homeless adolescents. Path models were used to examine concurrent relationships between youth's substance use and multiple aspects of their health and safety, including measures of psychological distress, housing risk and instability, and medical problems. Substance use was examined with both global (i.e., a composite of days of use across various drugs and alcohol) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Use of substances may be an important coping mechanism among these youth to decrease, change, or escape memories of childhood trauma; strains faced while homeless; and trauma and emotional discomfort associated with engagement in sexual risk behaviors or experience of victimization. Although there is limited extant research examining coping among homeless youth, findings of these studies have generally shown substances are used by this population group to manage their feelings, psychological distress, and emotional discomfort (Fisher, Florsheim, & Sheetz, 2005;Kidd, 2003;Rhule-Louie, Bowen, Baer, & Peterson, 2008). There is a need to understand the role using substances may have in relation to sexual risk behavior and sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Use of substances may be an important coping mechanism among these youth to decrease, change, or escape memories of childhood trauma; strains faced while homeless; and trauma and emotional discomfort associated with engagement in sexual risk behaviors or experience of victimization. Although there is limited extant research examining coping among homeless youth, findings of these studies have generally shown substances are used by this population group to manage their feelings, psychological distress, and emotional discomfort (Fisher, Florsheim, & Sheetz, 2005;Kidd, 2003;Rhule-Louie, Bowen, Baer, & Peterson, 2008). There is a need to understand the role using substances may have in relation to sexual risk behavior and sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of 285 homeless youth, participants used substances a mean of 22.7 days out of the previous 30 days [40]. Other studies have found that a little less than half of homeless youth use substances regularly, with approximately one-third of youth using substances on a daily or weekly basis [69,84].…”
Section: Substance Usementioning
confidence: 99%
“…Consequently, they make decisions about how and where to live during a time when their decision making and problem solving skills are immature [39]. These youth are at greater risk of making bad decisions and operating in high risk situations compared to their housed peers [40].…”
Section: Neurocognitive Developmentmentioning
confidence: 99%
“…33 In a study of street-involved adolescents, injection drug use was found to be negatively associated with the number of places in which the youth had stayed, yet positively associated with the probability of staying on the street. 34 In street-involved youth, including underage and older youth (aged 14 to 26), it was found that unstable housing (defined as living in a hostel or a shelter) was positively associated with greater number of sex partners. 30 In a prospective cohort study including 14-to 25-year-old street youth, homelessness episodes (at least 24 hours in the previous 6 months) were linked to increased risk of initiation into drug injection during follow-up.…”
Section: Introductionmentioning
confidence: 99%